Extrato da folha de Chenopodium ambrosioides linn (mastruz) atenua a perda óssea alveolar na periodontite experimental em ratos - Carneiro, Diego Thiers Oliveira (2020)
The Chenopodium ambrosioides L. plant has several biological actions, including the stimulation of new bone formation and prevention of bone loss. The main sequela of periodontal disease is the loss of the sustaining periodontium caused by the progression of the disease, which often leads to the loss of the dental element. Considering the biological actions of the mast in bone tissue metabolism, this work evaluated the anti-inflamatory and bone anti-resorptive actions in periodontitis with the treatment of the hydroalcoholic extract of the plant leaf administered orally in male Wistar rats. For this purpose, 30 male wistar rats (Rattus norvegicus) (200 g) were divided into 5 groups (n = 6): negative control group (CN) was not submitted to periodontal disease nor received any treatment; positive control group (CP) submitted to experimental periodontitis and treated with 2 ml / kg of 0.9% saline solution (vo); group (M3): had experimental periodontitis induced and was treated with the extract at a dose of 3 mg / kg; group (M10) subjected to induced periodontitis and was treated with the extract at a dose of 10 mg / kg; group (M30) subjected to induced experimental periodontitis and was treated with the extract at a dose of 30 mg / kg. The extractwas administered orally 30 minutes before the induction of periodontitis and daily until the 10th day, when on the 11th day the animals were euthanized. To analyze the type of flavonoid present in the extract, high performance liquid chromatography was performed. Upon euthanasia, the jaws were removed for macroscopic, histological and histometric analysis. The kidneys, liver and stomach were also collected to investigate the harmful potential caused by the administration of Mastruz. It was identified that the flavonoid Rutina was present in the extract in a major form. The results of this study showed that in the animals in the (M30) group there was a 41.3% decrease in bone loss, a 24.7% increase in the number of osteoblasts and a 51.3% decrease in osteoclasts by bone perimeter (p <0.05 ) when compared to the CP group. The animals that received the extract did not show any liver, kidney or gastric damage. In summary, we can conclude that Chenopodium ambrosioides L. extract has an anti-inflammatory and anti-resorptive effect in a dose-dependent manner, and can be an important pharmacological tool as an adjunct to the treatment of periodontitis.